2020
DOI: 10.1002/vzj2.20012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of water vapor adsorption in soils by means of a lysimeter and numerical modeling

Abstract: Daily temperature oscillations can cause adsorption (and desorption) of atmospheric water vapor by soils. The resulting daily fluctuations in the amount of liquid water in the soil can be measured by high-precision weighing lysimeters. We analyzed the data of a lysimeter in a sandy dune sediment in southern Spain using Codebright, a thermohydraulic numerical model for unsaturated flow that takes into account water, vapor, and heat transport in the soil, as well as soil-atmosphere interactions such as precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
(66 reference statements)
3
11
0
Order By: Relevance
“…At our study site Majadas, the largest annual NRWI contribution is adsorption with 21.2 mm year −1 . This value is relatively low, compared to sites close to the sea, where values of 81 mm year −1 (Saaltink et al, 2020), and 26 mm to 110 mm between April and October have been reported (Kosmas et al, 2001). But it matches well with observations from Qubaja et al (2020) that measured annual adsorption of 14 mm year −1 using flux chambers in a semiarid pine forest in Israel.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At our study site Majadas, the largest annual NRWI contribution is adsorption with 21.2 mm year −1 . This value is relatively low, compared to sites close to the sea, where values of 81 mm year −1 (Saaltink et al, 2020), and 26 mm to 110 mm between April and October have been reported (Kosmas et al, 2001). But it matches well with observations from Qubaja et al (2020) that measured annual adsorption of 14 mm year −1 using flux chambers in a semiarid pine forest in Israel.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, for adsorption, reported observation times differ. Kosmas et al (1998) observed the flux to occur mainly between 0:00 and 6:00 h and also Saaltink et al (2020) found suitable night-time conditions for adsorption through a reversed gradient of vapor concentration between soil and atmosphere from lysimeter observations and confirmed it with a fully coupled numerical model. Yet, Verhoef et al (2006) found adsorption occurring during the afternoon and ceasing at night.…”
Section: Discussionmentioning
confidence: 61%
“…At our study site of Majadas, the largest annual NRW contribution is adsorption (21.2 mm yr −1 ). This value is relatively low, compared to sites close to the sea, where values of 81 mm yr −1 (Saaltink et al, 2020) and 26 and 110 mm between April and October have been reported (Kosmas et al, 2001). But it matches well with observations from Qubaja et al (2020), who measured the annual adsorption of 14 mm yr −1 using flux chambers in a semi-arid pine forest in Israel.…”
Section: Non-rainfall Water Frequency Duration and Amountssupporting
confidence: 91%
“…The respective NRW is the adsorption of atmospheric vapor. However, despite being well understood at pore and laboratory scales (Tuller et al, 1999;Arthur et al, 2016), this process was underrepresented in NRW studies (Zhang et al, 2019b;Saaltink et al, 2020;Kohfahl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This means that vapour adsorption, measured by the lysimeter but not by TP1, can be neglected during rainfall events. Saaltink et al (2020) estimated vapour adsorption of 0.22 mm/day for the same site, which indeed is very low with respect to rainfall.…”
Section: Comparison Lysimeter With Tipping Bucket Pluviometer (Tp1)mentioning
confidence: 75%